Service user experiences of a novel in‐reach rehabilitation and recovery service for people with profound and enduring mental health needs. (27th March 2021) - Smith, Penn; Simpson, Lisa; Madill, Anna
Abstract: This article provides an organizational case study using exploratory qualitative and visual research methods. We address the research question: What are the experiences of service users who use a novel in‐reach rehabilitation and recovery service for people with severe and enduring mental health needs? Fifteen purposefully sampled service users were recruited from across a Service that is novel in embedding community sectors within inpatient provision. The sample reflects approximately the demographic of the Service and comprises: 10 men, 5 women; 12 white British, 3 ethnic minority; aged 18–60 years; and across inpatient care and supported community living. Photo‐elicitation was used to enrich data collection through lightly structured interviews focused on the images brought by participants. Interview transcripts were analysed using interpretative phenomenological analysis. Analysis indicates that participants oriented towards four 'meta‐questions': What does mental well‐being mean to you? What difficulties have you encountered? What do you appreciate about the Service? What do you need for change to occur? We also identified six themes which told the story of a journey. The journey begins with challenge and moves towards making connections with others. Here, power dynamics are often experienced and addressed in the development of a greater sense of independence . This then provides opportunities for raised awareness around possibilities of recovery and a new‐found hope . Our three main conclusions are all relevant to clinical practice: service users (a) place great importance on building relationships; (b) aspire to make informed choices throughout their recovery journey; and (c) desire greater transparency regarding treatment options.